2019
DOI: 10.1016/j.apsusc.2018.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the crystal structure of Ag2CO3 on the photocatalytic activity under visible light of Ag2CO3-Palygorskite nanocomposite material

Abstract: A B S T R A C TIn a companion paper, it has been demonstrated the remarkably beneficial effect of palygorskite clay (Pal) fibers as support material coupled to appropriate thermal treatments and aging under CO 2 atmosphere in monitoring the phase composition of Ag 2 CO 3 -Pal composite. In this new nanocomposite material, the structure of the functional component Ag 2 CO 3 can be controlled from 100% stable monoclinic (m) to 100% metastable hexagonal β through an adjusted mixture of m-and β-Ag 2 CO 3 . The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Specific thermal treatments under CO 2 coupled to aging for several hours to months were studied on the phase composition CO of pure Ag 2 CO 3 and (ii) of Ag 2 CO 3 supported palygorskite composites. This investigation help for establishing correlations between the phase composition of Ag 2 CO 3 in Ag 2 CO 3 /palygorskite new composites and their photocatalytic activity in the visible range which was reported in a companion paper (Lakbita et al, 2019). The importance of this study is reinforced by the photocatalytic properties since we found that the Ag 2 CO 3 -Pal nanocomposite in which Ag 2 CO 3 was single-phased and crystallized with the stable monoclinic structure was more active than the one crystallizing entirely with the metastable j3-Ag 2 CO 3 structure.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Specific thermal treatments under CO 2 coupled to aging for several hours to months were studied on the phase composition CO of pure Ag 2 CO 3 and (ii) of Ag 2 CO 3 supported palygorskite composites. This investigation help for establishing correlations between the phase composition of Ag 2 CO 3 in Ag 2 CO 3 /palygorskite new composites and their photocatalytic activity in the visible range which was reported in a companion paper (Lakbita et al, 2019). The importance of this study is reinforced by the photocatalytic properties since we found that the Ag 2 CO 3 -Pal nanocomposite in which Ag 2 CO 3 was single-phased and crystallized with the stable monoclinic structure was more active than the one crystallizing entirely with the metastable j3-Ag 2 CO 3 structure.…”
Section: Introductionmentioning
confidence: 58%
“…Subsequently the photocatalytic activity of these three categories of Ag 2 CO 3 /Pal nanocomposites with various phase compositions has been studied under visible light irradiation. Details reported in a companion paper (Lakbita et al, 2019) that the nanocomposite in which Ag 2 CO 3 was single-phased with the hexagonal structure was Jess active than the one crystallizing entirely with the stable monoclinic structure. How ever, the nanocomposite material containing a mixture of both Ag 2 CO 3 phases with a relative content of 32% of 13-and 68% of m-phase was found to be the most photoactive material of the series.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Silver-based materials such as AgCl, Ag 3 PO 4 , Ag 2 WO 4 , and Ag 2 CO 3 are promising photocatalysts, which can absorb visible light. Ag 2 CO 3 is a new type of high-efficiency visible light catalyst with a narrow band gap, which shows good activity in photocatalytic degradation of colored dyes . The separation efficiency of photogenerated electrons and holes can be improved by constructing a heterojunction. , The introduction of Ag 2 CO 3 into ZnO can notably improve the photocatalytic performance of ZnO because the charge separation will be greatly enhanced by the heterojunction between ZnO and Ag 2 CO 3 . , Therefore, a heterojunction combining ZnO with Ag 2 CO 3 can broaden the optical response range of ZnO, promote the separation of photogenerated electrons and holes, and markedly enhance the photocatalytic activity of ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…Ag 2 CO 3 is a new type of high-efficiency visible light catalyst with a narrow band gap, which shows good activity in photocatalytic degradation of colored dyes. 31 The separation efficiency of photogenerated electrons and holes can be improved by constructing a heterojunction. 32,33 The introduction of Ag 2 CO 3 into ZnO can notably improve the photocatalytic performance of ZnO because the charge separation will be greatly enhanced by the heterojunction between ZnO and Ag 2 CO 3 .…”
Section: Introductionmentioning
confidence: 99%